Evidence for Detection Bias by Medication Use in a Cohort Study of Breast Cancer Survivors. Issue 8 (1st March 2017) - Wirtz, Heidi S.; Calip, Gregory S.; Buist, Diana S. M.; Gralow, Julie R.; Barlow, William E.; Gray, Shelly; Boudreau, Denise M.
Abstract: In previous studies, we found modestly decreased and increased risks of second breast cancer events with the use of statins and antibiotics, respectively, after adjustment for surveillance mammography. We evaluated detection bias by comparing receipt of surveillance mammography among users of these 2 disparate classes of medication. Adult women diagnosed with early-stage breast cancer during 1990–2008 ( n  = 3, 965) while enrolled in an integrated health-care plan (Group Health Cooperative; Washington State) were followed for up to 10 years in the Commonly Used Medications and Breast Cancer Outcomes (COMBO) Study. Categories of antibiotic use included infrequent (1–3 dispensings/12 months) and frequent (≥4 dispensings/12 months) use, and categories of statin use included less adherent (1 dispensing/6 months) and adherent (≥2 dispensings/6 months). We examined associations between medication use and surveillance mammography using multivariable generalized estimating equations and evaluated the impact of adjusting for surveillance within Cox proportional hazard models. Frequent antibiotic users were less likely to receive surveillance mammography (odds ratio (OR) = 0.90, 95% confidence interval (CI): 0.82, 0.99) than were nonusers; no association was found among infrequent users (OR = 0.96, 95% CI: 0.90, 1.03). Adherent statin use was associated with more surveillance compared with nonuse (OR = 1.11, 95% CI: 1.01, 1.25), but less adherent statin use was not (OR = 1.03, 95% CI: 0.81, 1.31). No difference in associations between medications of interest and second breast cancer events was observed when surveillance was removed from otherwise adjusted models. The influence of detection bias by medication use warrants further exploration.